2017
DOI: 10.1097/qai.0000000000001153
|View full text |Cite
|
Sign up to set email alerts
|

Reduced IL-7R T Cell Expression and Increased Plasma sCD127 in Late Presenting HIV-Infected Individuals

Abstract: Severely altered IL-7R expression was found in late presenters, and associations between IL-7R expression and thymic output after 24 months of suppressive cART indicate an impact of a IL-7 response for the long term de novo production from thymus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…demonstrated that neither the plasma level of IL‐7 nor CD127 expression on CD4 + T cells was associated with an increase in the total CD4 + T‐cell count after initiation of ART. In contrast, they found positive associations between baseline CD127 density on CD4 + T cells and an increase in CD4 + RTE cell counts and naïve CD4 + T‐cell counts after 2 years of effective ART, indicating that CD127 expression on CD4 + T cells is a predictor of increased thymic output after 2 years of suppressive ART . Furthermore, a few studies have found that in INRs, plasma levels of IL‐7 were elevated and CD127 expression both on CD4 + and CD8 + T cells was decreased; however, there was no statistically significant correlation between the baseline plasma IL‐7 level and absolute CD4 + T‐cell count after successful ART .…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 93%
See 1 more Smart Citation
“…demonstrated that neither the plasma level of IL‐7 nor CD127 expression on CD4 + T cells was associated with an increase in the total CD4 + T‐cell count after initiation of ART. In contrast, they found positive associations between baseline CD127 density on CD4 + T cells and an increase in CD4 + RTE cell counts and naïve CD4 + T‐cell counts after 2 years of effective ART, indicating that CD127 expression on CD4 + T cells is a predictor of increased thymic output after 2 years of suppressive ART . Furthermore, a few studies have found that in INRs, plasma levels of IL‐7 were elevated and CD127 expression both on CD4 + and CD8 + T cells was decreased; however, there was no statistically significant correlation between the baseline plasma IL‐7 level and absolute CD4 + T‐cell count after successful ART .…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 93%
“…56,57 It has been reported that in In contrast, they found positive associations between baseline CD127 density on CD4 + T cells and an increase in CD4 + RTE cell counts and naïve CD4 + T-cell counts after 2 years of effective ART, indicating that CD127 expression on CD4 + T cells is a predictor of increased thymic output after 2 years of suppressive ART. 60 Furthermore, a few studies have found that in INRs, plasma levels of IL-7 were elevated and CD127 expression both on CD4 + and CD8 + T cells was decreased; however, there was no statistically significant correlation between the baseline plasma IL-7 level and absolute CD4 + T-cell count after successful ART. 61 Furthermore, others have shown a positive association 59,62 or a negative association [63][64][65] ECs is equivalent to that in healthy subjects.…”
Section: Cytokinesmentioning
confidence: 99%
“…Implementation of D2C varies across jurisdictions, and published reports describe successful re-linkage outcomes from 3 main D2C referral sources: (1) health care providers [ 9–11 ], (2) HIV surveillance [ 12–16 ], and (3) a combination approach in which a list of patients lost to follow-up from an HIV care clinic is matched to HIV surveillance [ 3 , 6 , 17–19 ]. Several jurisdictions cite inefficiencies of surveillance-only-generated referrals because of the overidentification of “current to care” PWH who appear to be NIC by surveillance because of delayed lab reporting or relocation across state lines [ 11 , 13 , 14 , 16 , 20 , 21 ].…”
mentioning
confidence: 99%
“…It is necessary to identify the main CD4+ and CD8+ T-cell subsets which are affected by HCV infection. In addition, studies of functional changes in T-lymphocytes like exhaustion [159][160][161], senescence [162][163][164], and loss of cytokine receptors [165,166] must occur. It is also important to understand the nature of the immune system activation in HIV/ HCV coinfection which is important in predicting the development of non-AIDS-defining diseases.…”
Section: Resultsmentioning
confidence: 99%